Migration and infectious disease risk: knowledge and perception among European students. (30th September 2020) - Marconi, D; Casigliani, V; Mazzilli, S; Lopalco, P L
Abstract: Background: In the past years migration has increasingly affected the European continent. The concerns of the local population about infection spread by migrants may increase unjustified stigma. Literature has shown that stigma is a determinant of health. The aim of our study was to assess the knowledge and risk perception of infectious disease introduced by migration. Methods: Between January and February 2020 we conducted an online survey in Italian and Spanish University students. We collected data on demographics, perception and knowledge of transmission of infectious diseases introduced by migration. We performed a descriptive and a risk factors analysis to assess correlation between our variables. Results: We collected 1397 answers: 1022(73.16%) from Italian students (F:668/1022, M:341/1022, others:13/1022) and 375(26.84%) from Spanish students(F:253/375, M:119/375, others:3/375) The median age was 24 for Italy and 22 for Spain. In Italy and Spain, respectively, 353/1022(34, 54%), 145/375(38, 67%) students were from the healthcare area, 316/1022(30, 92%), 74/375(19, 73%) the scientific area, 349/1022(34, 15%), 108/375(28, 80%) the non-scientific area and 4/1022(0, 39%), 48/375(12, 80%) from others area. We found a statistically significant correlation between the knowledge of infectious diseases and the perception of the infectious risk associated with migration. This correlation was not confirmed for the area of study. Healthcare students had the best levels of knowledge and perception of the migratory phenomenon, but the higher perception of infectious risk. Exposure to the news was associated with the worst perception of the migratory phenomenon and the infectious risk (p < 0.001). Conclusions: Our study showed that students in the health area had the highest risk perception of infectious diseases. Therefore, the introduction of the course on migration medicine and the increase of practical training could help to reduce the altered risk perception of infectious diseases. Key messages: The introduction of the course on migration medicine and the increase of practical training could help to reduce the altered risk perception of infectious diseases in healthcare students. Exposure to the news has a negative effect on the perception of the migratory phenomenon and the ìnfectious disease.